Constructive journalism and its effects on environmental discourses - Lekshmi Priya Sanal; I. Arul Aram (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
Concerning the existence of all living beings, environmental issues take a crucial standpoint in the area of constructive journalism. Through positive psychology and solution-based approaches, it moves from the rigid ethical tenets of objectivity and impartiality, and employs practices based on reflexivity and advocacy for social concerns including pressing environmental issues. Can this change of journalistic narrative be considered significant? If so, does it imply any shifts in existing media culture that embodies a new set of ethics? This paper studies the ethics emerging out of constructive journalism based on environmental discourses and reviews 25 global environmental stories with constructive attributes through content analysis. With non-alarmist headlines, solutions-based and restorative approaches, and comprehensive narratives, it was found that these articles did not flout any ethical principles besides environmental advocacy. A shift in ethical code is recommended to entirely accommodate reflexive and transformative narratives in the field of journalism.